The impossible no: disciplinary boundaries and the problem of science in literary and science fiction studies. - Bartolotta, Simona (Neohelicon, 2025)
In this article, I examine the widespread sense of distrust that the literary humanities, with a specific emphasis on science fiction studies, have long expressed towards science's claims of objectivity and neutrality. I argue that such distrust is chiefly tied to two factors: a simplistic, almost caricaturized understanding of the general nature of scientific inquiry and related concepts, and a tendency to conflate the politics and ethics of scientific practice and applications with the epistemic workings of science. I begin by offering a critique of the latter fallacy, identified as a fallacy in fact/value distinction, and of one of its most pernicious corollaries, namely the politicization of this fallacy via claims concerning the perceived oppressive and imperialist character of so-called 'Western' science. In the second part of the article, I ground this analysis in an extensive investigation of how such mischaracterizations have come to radically inform the field of science fiction studies, often through their institutionalization in Kuhnian philosophy of science, the Strong Programme in the sociology of scientific knowledge, and more generally the field of science and technology studies. Finally, I offer practical strategies for re-establishing fruitful interdisciplinary communication.